The nature of transformation: Environmenatal adult and popular education / Darlene E. Clover y otros - Clover, Darlene E. Follen, Shirley. Hall, Budd (Canadá: University of Toronto Press, Inc, 1998)
Trata sobre un enfoque detallado sobre cómo las empresas pueden navegar con éxito en la era digital.
1. Educational theories and principles from wish we work 2. The power of passion
incluye índice
Col. Agro
Keywords: 1.ENVIRONMENTAL EDUCATION 2. WOMEN AS ENVIRONMENTAL EDUCATION